Correlations between clinical activity, endoscopic severity, and biological parameters in colonic or ileocolonic Crohn's disease. A prospective multicentre study of 121 cases. The Groupe d'Etudes Thérapeutiques des Affections Inflammatoires Digestives. Issue 2 (February 1994) - Cellier, C; Sahmoud, T; Froguel, E; Adenis, A; Belaiche, J; Bretagne, J F; Florent, C; Bouvry, M; Mary, J Y; Modigliani, R
Abstract : The relationships between clinical activity, endoscopic severity, and biological parameters in Crohn's disease have not been thoroughly investigated and a link was therefore sought between these three elements. The following parameters were determined simultaneously in 121 consecutive patients with colonic or ileocolonic Crohn's disease: Crohn's disease activity index, Crohn's disease endoscopic index of severity, and serum albumin, alpha 2-globulin, alpha 1-antitrypsin, orosomucoid, C reactive protein, erythrocyte sedimentation rate, platelets, lymphocyte and polymorphonuclear cell counts, haematocrit, and faecal alpha 1-antitrypsin concentration. The distribution of these parameters was studied and transformation was used so that data matched the normal distribution closely. A weak but significant correlation (r = 0.32; p < 0.001) was found between clinical and endoscopic indices in the whole group of patients and this correlation seemed to be homogenous in various patient subgroups (clinically quiescent or active disease, pure colonic disease, untreated patients). Endoscopic or clinical indices were also found to be weakly linked with biological parameters (r < 0.50). Stepwise linear regression identified C reactive protein as predictive of the clinical index, and, successively, alpha 2-globulin, erythrocyte sedimentation rate, faecal alpha 1-antitrypsin, serum orosomucoid, and alpha 1-antitrypsin as predictive of the endoscopic index. Both predictions were poor--the biological variables accounting for only 22 and 44% respectively of the clinical and endoscopic index variations. In conclusion, Crohn's disease clinical activity seems to be virtually independent of the severity of the mucosal lesions and biological activity.